For the computation of the lower (attracting) fixpoint $L_0$ for $b^{L_0} = L_0 $ (where the base $b$ is in the range for convergence $1 \lt b \lt e^{1/e}$) there is the simple formula $$L_0 = \exp(-W(-\log(b))) \qquad \qquad \text{where $W$ is the Lambert-W-function}$$ or if we directly use the logs for $b$ and $L$ writing $\beta := \log(b)$ and $\lambda := \log(L)$ $$\lambda_0 = -W(-\beta) \phantom{\qquad \qquad \text{where $W$ is the Lambert-W-function}}$$ (This has also the nice property that $\beta = \lambda_0 / L_0 $ or $b=L_0^{1/L_0}$.)

I think there is a related formula for the upper (repelling) fixpoint $L_1$ too, but I can't remember it from the top of my head (some simple variations didn't work so far). Before beginning a long search in older texts and program-sources (the searchkey were much un-sharp) - could someone refresh my memory? A reference would suffice...

Example: let $b=\sqrt 2$ then $L_0 = 2$ because $b^2 = 2$ and $L_1=4$ because $b^4 = 4$

Remark: I know how to approximate $L_1$ using the Newton-algorithm - I specifically think to remember that there is some variant with the Lambert W (which is what I want here)


2 Answers 2


Yes. If you use the other real-valued branch of $W$, denoted $W_{-1}$, you will get this fixed point:

$$\lambda_U = -W_{-1}(-\beta)$$


$$L_U = \exp(-W_{-1}(-\log(b)))$$.

But I do not know if or believe that $W_{-1}$ can be expressed through $W = W_0$, the principal branch (unlike simpler multivalued relations like $\sqrt{...}$ and $\log$ in the complex plane.).

  • $\begingroup$ Ahh, thank you. I had tried $W_1()$ instead... I think now, there was even a routine to compute this easily in the "Mount Meru" of information in tetration-forum. I'll see... $\endgroup$ Oct 7, 2017 at 7:31

Another solution which does not involve the LambertW function involves generating the following series inverse, which I will explain in steps. $$f=\sqrt{2(\exp(x)-x-1)};\;\;\;\;\text{xfixed}=f^{-1}(x)$$ $$\text{xfixed}= x - \frac{x^2}{6}+ \frac{x^3}{36} - \frac{x^4}{270} + \frac{x^5}{4320} + \frac{x^6}{17010} - \frac{139x^7}{5443200} ...$$ In pari-gp, this series would be "serreverse(sqrt((exp(x)-x-1)*2))". I don't have a closed form for the series. By plugging both square roots into this series, you can get either fixed point L for the base=b.

$$L_b = \frac{\text{xfixed}\left(\pm\sqrt{-2(\ln(\ln(b))+1)}\right)-\ln(\ln(b))}{\ln(b)}$$

One interesting thing about the square root radical is that if $b=\exp(1/e)$, then the radical is zero, which makes sense since $b=\exp(1/e)$ has only one fixed point. Using a 16 term series for xfixed, I got about 19 decimal digits of precision for the two fixed points of $b=\sqrt{2}$ So, why does this work? We must first show that iterating $$z \mapsto b^z$$ is exactly congruent with iterating $$y \mapsto \exp(y)+k;\;\;k=\ln(\ln(b));\;\;\;y=z\ln(b)+\ln(\ln(b))$$

So then our fixed point problem for $z \mapsto b^z$ becomes equivalent to finding the fixed point for $y \mapsto \exp(y)+k$. If we have the fixed point for y, then we can get the fixed point for $z \mapsto b^z$ by using this equation based on the congruency. $$z = \frac{y-\ln(ln(b))}{\ln(b)}$$

Next, we do some algebra to get the fixed point for $$y = \exp(y)+k;\;\;\;k=\ln\ln(b))$$ $$y = k + 1 + y + \frac{y^2}{2} + \frac{y^3}{6} + \frac{y^4}{24} + \frac{y^5}{5!} ...$$ $$ -(k+1) = \frac{y^2}{2} + \frac{y^3}{6} + \frac{y^4}{4!} ...$$ $$ -2(k+1) = y^2 + \frac{2y^3}{6} + \frac{2y^4}{24} + \frac{2y^5}{5!} ...$$ Now we take the square root of both sides. $$ \sqrt{-2(k+1)} = f(y) = y\cdot \sqrt{1 + \frac{2y}{6} + \frac{2y^2}{24} + \frac{2y^3}{5!} ...}$$ $$ \sqrt{-2(k+1)} = f(y) = y + \frac{y^2}{6} + \frac{y^3}{36} + \frac{y^4}{270} + \frac{y^5}{2592} + \frac{17y^6}{544320} + \frac{11y^7}{5443200}+...$$

The square root term on the right has a nice defined formal Taylor series in y; which leads exactly to the $f$ in the 2nd line of my post. So then we can get k from y. We need the reverse, so we take the inverse of Taylor series for f. $$ y = f^{-1}\left(\pm\sqrt{-2(k+1)}\right)=f^{-1}\left(\pm\sqrt{-2(\ln(ln(b))+1)}\right)$$

Now we have the fixed point $y=\exp(y)+k$, and the final step is to generate the fixed point $z=b^z$ from y using $z = \frac{y-\ln(ln(b))}{\ln(b)}$

  • $\begingroup$ A miraculous method, indeed... $\endgroup$ Oct 8, 2017 at 21:51
  • $\begingroup$ Thanks Gottfried :) This equation also works for both real and complex bases for b. $\endgroup$
    – Sheldon L
    Oct 8, 2017 at 21:53

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.